CAE Applications in a Thermoforming Mould Design - A. R., Marjuki; Farah Amira, Mohd Ghazali; N. M., Ismail; S., Sulaiman; Ismail, Mohd Khairuddin; Anwar, P. P. Abdul Majeed; Abdul Aziz, Jaafar; F., Mustapha; Shahnor, Basri (IOP Publishing, 2016)
Preparation of honeycomb layer is a critical step for successful fabrications of thermoformed based sandwiched structures. This paper deals with an initial investigation on the rapid manufacturing process of corrugated sheet with 120o dihedral angles. Time history of local displacements and thickness, assuming viscous dominated material model for a 1mm thick thermoformable material, was computed by using ANSYS R Polyflow solver. The quality of formed surfaces was evaluated for selection of mould geometry and assessment of two common variants of thermoforming process. Inadequate mesh refinement of a membrane elements produces satisfactorily detailing and incomplete forming. A perfectly uniform material distribution was predicted using drape forming process. However, the geometrical properties of vacuum formed part are poorly distributed and difficult to control with increasing inflation volumes. Details of the discrepancies and the contributions of the CAE tool to complement traditional trial and error methodology in the process and design development are discussed.